In vitro antimicrobial activity of total extracts of the leaves of Petiveria alliacea L. (Anamu) - Ania Ochoa Pacheco; Jorge Marín Morán; Zenia González Giro; Adrian Hidalgo Rodríguez; Rachel Juliet Mujawimana; Karel Tamayo González; Sandra Sariego Frómeta (Brazilian Journal of Pharmaceutical Sciences, 2013)
The antimicrobial activity of 13 total extracts was evaluated, 10 soft extracts (B) and 3 blended extracts (E) prepared from dry and fresh leaves of Petiveria alliacea L. Various solvents were used for their preparation: hydroalcoholic solution at 30%, 80% and isopropyl alcohol. The antimicrobial effect of the extracts was tested by means of the method of Kirby-Bauer, using four bacterial strains from the ATCC collection (Escherichia coli, Staphylococcus aureus, Enterococcus faecalis and Pseudomonas aeruginosa) and a leveduriform fungus (Candida albicans). The following quality control parameters were determined for most active extracts: physical, physical-chemical and chemical parameters. The results were: nine extracts showed antibacterial activity, being the most concentrated (B8 and E3), the ones with the highest activity in the presence of the bacteria tested; the effect of blended extracts (E1, E2 and E3) was greater in the presence of P. aeruginosa. Blended extracts are considered more potent and active than soft extracts. No antifungal activity was obtained for both types of extracts. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined for both extracts, with the following results: MIC-soft extracts (>100 mg/mL), blended extracts (>50 mg/mL); MBC-soft extracts (≥400 mg/mL), blended extracts (≥200 mg/mL) based on fresh leaves.